Pengaruh Insentif, Motivasi Kerja, dan Loyalitas Karyawan Terhadap Kinerja Karyawan Pada PT. PNM Ulamm Surabaya - oktaviani, berliana; Pratiwi, Ni Made Ida; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
Human resources have a very important role in achieving company goals, because humans become planners, actors and determinants realization of the company’s goals. Based on company data PT. PNM Ulamm Surabaya employee performance experienced a drastic decline resulting in decreased employee performance in 2022. This research aims to find out if there is an influence of Incentive, Work Motivation and Employee Loyalty on Employee Performance at PT. PNM Ulamm Surabaya. This study uses a type of quantitative research. The sample used in this study as many as 80 employees of PT. PNM Ulamm Surabaya. Using a non-probability sampling method (no sampling random) with saturated sampling technique. data collection methods using questionnaire. The data analysis technique used in this research is test classic assumptions, multiple linear regression test and hypothesis testing. The results of this study shows that first, partially Incentives have a significant effect on Employee performance. Second, partially work motivation has a significant effect on Employee Performance. Third, partially influential Employee Loyalty significant to Employee Performance. Then the results of the F test show that Incentives, Work Motivation and Employee Loyalty together (simultaneously) significant effect on employee performance at PT. PNM Ulamm Surabaya. Therefore, companies must pay attention to performance such as aspects of quality and quantity of work, provide employee job training, provide tool facilities transportation for employees working in the field, creating integrity measurement formats done by the HR department (human resources) as well as making jargoun that contains the employee’s cultural values ​​and places the jargoun in work space to remind employees of the company’s cultural values.